Poziom wskaźnika szybkiej płynności finansowej a efektywność przedsiębiorstw rolniczych - Wasilewski, Mirosław (Quick Ratio Level and Agricultural Enterprises Effectiveness, 2007)
The paper presents relations between size of a quick ratio and agricultural enterprises' effectiveness. The ratio diversified effectiveness of use of production factors. Return on fixed assets, equity and sales as well as economic labour efficiency were increasing while the quick ratio was growing. Enterprises without current debts presented lower profitability of production factors in comparison to enterprises of the ratio value greater than 0.8. Moreover, enterprises without current debts were characterized by the highest return on current assets. The value of quick ratio that had been advised at a level of 1.0 did not make the highest effectiveness available. It was found that the definition of the ratio's optimum has been less important than an estimation of a minimum value of the ratio that would let an enterprise run profitable activity. The ratio calculated with net profit in agricultural enterprises should amount to minimum 0.5, and when calculated with profit from sales -minimum 0.8.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 441-452